Recent advances in the structures and bioactivities of benzopyrans derived from marine fungi: a review - Xi, Yidan; Wang, Huannan; Sun, Lixiang; Ma, Xueyang; Zhang, Shuncun; Zhang, Zhen (Frontiers in Pharmacology, 2024)
Marine fungi represent a treasure trove of bioactive secondary metabolites, with benzopyran compounds emerging as a significant class of these natural products. This review delves into the structural diversity, biological activities, and sources of benzopyran compounds, highlighting their isolation from marine fungi inhabiting diverse environments such as sponges, marine sediments, algae, mangroves, and corals. Our literature search, conducted from 2000 to 2023, has identified a wealth of benzopyran compounds, showcasing their potential as lead compounds in drug development. The characteristics of benzopyran from marine fungi are explored, encompassing various subclasses such as chromones, isocoumarins, citrinins, and other related compounds. These compounds exhibit a remarkable chemical diversity, which is crucial for their diverse biological activities. The potential of benzopyran compounds in drug development is also discussed, emphasizing their roles in anti-tumor, antibacterial, anti-inflammatory, and enzyme inhibitory activities. In recent years, a remarkable 210 bioactive benzopyran compounds have been isolated from the secondary metabolites of marine fungi. These findings underscore the importance of marine fungi as a source of novel bioactive compounds, offering a plethora of potential lead compounds for the development of marine-derived drugs. This review aims to provide a comprehensive overview of the current state of research on benzopyran compounds, setting the stage for future advancements in the field of marine natural products.